Konsep Kurikulum 2013 Ditinjau Dari Kodrat Manusia Menurut Jean Jacques Rousseau - Firmanians Tuerah (Jurnal Manajemen Pendidikan Kristen, 2021)
ABSTRACT. The 2013 Curriculum is expected to produce Indonesian people who we inspire together. Therefore, this article explores the human idea contained in the Kurikulum 2013. This can be achieved by using an approach to human philosophy from Jean Jacques Rousseau with methodical elements of interpretation, internal coherence, description and reflection. Based on the analysis that has been done, there are several things that can be concluded from the results of the study. First, 2013 Curriculum which is based on character and creativity is an attempt to take responsibility for oneself in freedom. Second, efforts to develop students' character and creativity must be in the context of fighting for the "general will". Third, creativity or good self-character will create the common good.